Functional Expression of Programmed Death-Ligand 1 (B7-H1) by Immune Cells and Tumor Cells - Gibbons Johnson, Rachel M.; Dong, Haidong (Frontiers in Immunology, 2017)
The PD-1 and its ligand PD-L1 (B7-H1) signaling pathway has been the focus of much enthusiasm in the fields of tumor immunology and oncology with recent FDA approval of the anti-PD-1 antibodies pembrolizumab and nivolumab and the anti-PD-L1 antibodies durvalumab, atezolimuab, and avelumab. These therapies, referred to here as PD-L1/PD-1 checkpoint blockade therapies, are designed to block the interaction between PD-L1, expressed by tumor cells, and PD-1, expressed by tumor-infiltrating CD8+ T cells, leading to enhanced anti-tumor CD8+ T cell responses and tumor regression. The influence of PD-L1 expressed by tumor cells on anti-tumor CD8+ T cell responses is well characterized, but the impact of PD-L1 expressed by immune cells has not been well defined for anti-tumor CD8+ T cell responses. Although PD-L1 expression by tumor cells has been used as a biomarker in selection of patients for PD-L1/PD-1 checkpoint blockade therapies, patients whose tumor cells lack PD-L1 expression often respond positively to PD-L1/PD-1 checkpoint blockade therapies. This suggests that PD-L1 expressed by non-malignant cells may also contribute to anti-tumor immunity. Here we review the functions of PD-L1 expressed by immune cells in the context of CD8+ T cell priming, contraction, and differentiation into memory populations, as well as the role of PD-L1 expressed by tumor cells in regulating anti-tumor CD8+ T cell responses.